2013
DOI: 10.3109/13880209.2013.766220
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of hypoglycemia or hypotension in older adults during 6 months of flax lignan supplementation in a randomized controlled trial: A safety evaluation

Abstract: Context: The natural health product, BeneFlax, is a standardized flaxseed [Linum usitatissimum L. (Linaceae)] lignan enriched product with evidence of product quality and known quantity of the bioactive component, lignan. The acceptance of this natural health product for its various health benefits requires greater evidence of its safety in the general population. Objective: We determined whether flaxseed lignan causes clinical hypoglycemia or hypotension in healthy older adults as an important aspect of safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Other studies have demonstrated improved glycemic control (Pan et al, 2007), decreased blood glucose levels (Zhang et al, 2008), reduced CRP (Hallund, Tetens, Bugel, Tholstrup, and Bruun, 2008;) and a mild attenuation in DBP (Cornish et al, 2009) with a lignan-supplemented diet. An additional study noted that Beneflax, a lignan supplement containing 543 mg/day of flaxseed lignan per tablet (Cornish et al, 2009), does not pose a risk for hypotension or hypoglycemia in healthy older adults (Billinsky et al, 2013).…”
Section: Lignansmentioning
confidence: 99%
“…Other studies have demonstrated improved glycemic control (Pan et al, 2007), decreased blood glucose levels (Zhang et al, 2008), reduced CRP (Hallund, Tetens, Bugel, Tholstrup, and Bruun, 2008;) and a mild attenuation in DBP (Cornish et al, 2009) with a lignan-supplemented diet. An additional study noted that Beneflax, a lignan supplement containing 543 mg/day of flaxseed lignan per tablet (Cornish et al, 2009), does not pose a risk for hypotension or hypoglycemia in healthy older adults (Billinsky et al, 2013).…”
Section: Lignansmentioning
confidence: 99%
“…Many of these studies have reported no genotoxic, haematological or behavioural changes following consumption of flaxseed or flaxseed products ( 10 12 ) . Billinsky et al ( 13 ) reported no evidence of hypoglycaemia or hypotension in healthy older adults when the flaxseed lignan-enriched complex, Beneflax, was administered for 6 months; however, other studies have reported some adverse reactions in special populations such as pregnant and lactating women ( 14 16 ) . In general, safety and efficacy data on flaxseed lignans are inadequate.…”
mentioning
confidence: 99%
“…Recently, a high SDG lignan supplement was assessed for its hypotensive effects in a healthy population >48 years of age [33]. BeneFlax is a commercially available source of SDG lignan that provides 543 mg of SDG in a single tablet.…”
Section: Flaxseed Lignansmentioning
confidence: 99%